Observed Performance of Highway Embankment over Soft Marine Clay: A Case Study in Wenzhou, China - Xia Bian; Jin-Kai Yan; Wei Zhang (Advances in Civil Engineering)
This paper presents a case history of observed performance of highway embankment over soft marine clay in Wenzhou, China. During the embankment construction, the changes of ground settlement, ground displacement, and lateral displacement of subsoil with the construction time were monitored and analyzed. The monitoring results indicate that the ground settlement and lateral displacement of subsoil account for about 75% in the process of embankment construction. The measured maximum values of ground settlement, ground displacement, and lateral displacement of subsoil are 37.88 mm, 21.50 mm, and 23.56 mm, respectively. After the completion of the embankment construction, the settlement gradually tended to be stable. It is suggested that the monitoring data of settlement and displacement of embankment are smaller than the design requirements, and the embankment stability is also ensured.